Pengembangan Media Video Animasi Berbasis Kearifan Lokal Riau pada Materi Pecahan untuk Siswa SD Kelas IV SDN 001 Khairiah Mandah - Komang Rahma Triningsih; Siti Quratul Ain (YASIN, 2026)
The development of mathematics learning media based on digital technology and local culture is important because fraction learning in elementary schools is still often delivered conventionally and is less contextual. This study aims to develop animated video media based on Riau local wisdom on fraction material for Grade IV students at SDN 001 Khairiah Mandah. This study used a Research and Development (R&D) method with qualitative and quantitative approaches and an ADDIE model modified up to the Analysis, Design, and Development stages. The research subjects included Grade IV teachers, Grade IV students, and validators consisting of material experts, media experts, and language experts selected purposively. Data were collected through interviews, validation questionnaires, tests, and documentation, and were then analyzed descriptively, qualitatively, and quantitatively using validation percentages. The results showed that the animated video media obtained an average validation score of 87.50% in the very valid category, comprising the media aspect at 89.58%, the language aspect at 91.67%, and the material aspect at 81.25%. These findings indicate that animated video media based on Riau local wisdom is feasible for use as an alternative mathematics learning medium that is engaging, concrete, and contextual for fraction material. This study contributes to the development of mathematics learning media based on local culture in elementary schools. As a practical implication, teachers can use animated video media to present fraction learning that is more closely connected to students’ cultural experiences, while further research is recommended to test the effectiveness of the media with a broader student population.